IFU spectroscopy of southern PNe – VII. Photoionization modelling of intermediate excitation class objects. Issue 3 (21st January 2019) - Ali, A; Dopita, M A
ABSTRACT: We present integral field unit spectroscopic observations of southern Galactic planetary nebulae (PNe) IC 2501, Hen 2-7, and PB 4. The goal of studying these objects together is that, although they have roughly similar intermediate excitation and evolution of central stars (CSs), they display very different evolution in their nebular structure that needs to be understood. The morphologies and ionization structures of the objects are investigated using a set of emission-line maps representative of the different ionization zones. We use those in order to construct two-zone self-consistent photoionization models for each nebula to determine new model-dependent distances, progenitor luminosities, effective temperatures, and CS masses. The physical conditions, chemical compositions, and expansion velocities and ages of these nebulae are derived. In Hen 2-7 we discover a strong poleward-directed jet from the presumed binary CS. Oxygen and nitrogen abundances derived from both collisionally excited and recombination lines reveal that PB 4 displays an extreme abundance discrepancy factor, and we present evidence that this is caused by fluorescent pumping of the O ii ion by the EUV continuum of an interacting binary CS, rather than by recombination of the O iii ion. Both IC 2501 and PB 4 were classified by others as Weak Emission Line Stars (WELS). However, our emission-line maps show that their recombination lines are spatially extended in both objects, and are therefore of nebular rather than CS origin. Given that we have found this result in a number of other PNe, this result casts further doubt on the reliability, or even the reality, of the WELS classification.